2019
DOI: 10.1063/1.5119191
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of HO2 radicals produced in an atmospheric pressure plasma using Faraday rotation cavity ring-down spectroscopy

Abstract: A scalable arbitrary waveform generator for atomic physics experiments based on fieldprogrammable gate array technology Review of Scientific Instruments 90, 043101 (2019);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…An expansion of the standard polarimetric methods came with the introduction of Cavity Ring Down Polarimetry (CRDP) by Vaccaro and co-workers in the early 2000s [10], which used a linear optical cavity to enhance polarimetric signals, and has produced a variety of optical rotation measurements in the gas and liquid phase [11,12,13,14,15,16]. Linear cavities have also been used to measure the Faraday Effect in gases [17,18,19]. In 2014, our group improved CRDP by using a ring cavity, allowing counter-propagating laser beams, and an intracavity Faraday Effect.…”
mentioning
confidence: 99%
“…An expansion of the standard polarimetric methods came with the introduction of Cavity Ring Down Polarimetry (CRDP) by Vaccaro and co-workers in the early 2000s [10], which used a linear optical cavity to enhance polarimetric signals, and has produced a variety of optical rotation measurements in the gas and liquid phase [11,12,13,14,15,16]. Linear cavities have also been used to measure the Faraday Effect in gases [17,18,19]. In 2014, our group improved CRDP by using a ring cavity, allowing counter-propagating laser beams, and an intracavity Faraday Effect.…”
mentioning
confidence: 99%
“…In particular, Westberg and Wysocki 59 using an optical cavity with F ≈ 50000 demonstrated Faraday optical rotation sensitivities of ∼ 1.3 × 10 −9 rad/ √ Hz (per cavity round-trip, for 1 s of integration time), at 762 nm. Similarly, Gianella et al 32 using an optical cavity with F ≈ 175000, demonstrated almost identical Faraday optical rotation sensitivities of ∼ 1.24 × 10 −9 rad/ √ Hz (per cavity round-trip, for 1 s of integration time), at 1506 nm. Using our analysis on the fundamental frequency sensitivity limits of CRDP ("Prediction" point in Fig.…”
Section: B Cw-crdp Experimental Sensitivity Limitsmentioning
confidence: 70%
“…We start by discussing the theory of CW-CRDP. Although several extended analyses of the theory behind CW-based cavity-enhanced polarimetric schemes exist in the literature 32,[39][40][41] , we repeat here key theoretical aspects to clarify the necessary terminology and concepts required to understand the experimental principles of the CW-CRDP technique.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the sensitivity of current system for HO 2 detection is lower than that attained in experiments using cavity ring-down spectroscopy in the near infrared region 37,38 , the sensitivity of the adopted method can be improved by coupling the dual-comb laser with a cavity-enhanced reaction cell.…”
Section: Discussionmentioning
confidence: 95%